Creativity and knowledge creation: the moderated mediating effect of perceived organizational support on psychological ownership. Issue 6 (3rd June 2020) - Yoon, Sun Kyung; Kim, Jae Hyun; Park, Jung Eun; Kim, Chan Ju; Song, Ji Hoon
Abstract : Purpose: The purpose of this study is to examine the influences of creativity, psychological ownership (PO) and perceived organizational support (POS) on knowledge creation, using the integrative systems model of creativity. Design/methodology/approach: A survey was used to collect data from 188 workers in Korean public service organizations. Analyses, including bootstrapping and hierarchical regression analysis, were performed to determine the mediating effect of PO and also the moderating and the moderated mediating effects of POS. Findings: The results showed that PO mediates partially between creativity and knowledge creation and that POS moderates the relationship between PO and knowledge creation. Notably, the moderated mediating effect of POS was only significant when employees had a high level of POS. Practical implications: The findings suggest that creativity dissemination requires employees' social consciousness, collaborative interactions and organizational support. The results imply that human resource development (HRD) practitioners need to cultivate the creativity capacity in the organization. Originality/value: This study discusses the effects of PO and POS on creative performance, which HRD professionals and organizational leaders draw attention to for organizational development. Implications for organizational composition and interventions to enhance creative performance are provided.